Phytoassisted synthesis of biogenic ZnO nanoparticles using Annona squamosa L. bark extract: characterization and its application studies - Koushika Saravanan; Vanaraj Sekar; Mohammed Ali Alshehri; Chellasamy Panneerselvam; Preethi Kathirvel (Green Chemistry Letters and Reviews)
The current research aspires to explore the novel utilization of Annona squamosa bark extract consisting of various phytochemical components as a capping agent with zinc acetate as a precursor to form zinc oxide particles. The origination of ZnO NPs is implied by the UV-Visible absorption band at 357 nm and the distinctive XRD peaks at the appropriate positions. The occurrence of highly crystalline, hexagonal phase, and impurity-free As-ZnO NPs was made apparent by the XRD pattern. Employing XRD, the average particle size from the crystallites has been identified to be 56.23 nm. The FTIR spectral analysis verified the existence of biomolecules on the ZnO NP surface. These ZnO NPs have hexagonal structures and flake-like morphology as revealed by FESEM analysis, respectively. EDS study proved the existence of Zn (51.77 weight%) and O (20.56 weight%). The fabricated As-ZnO NPs demonstrated outstanding efficacy in various biological applications, spanning in vitro antimicrobial, antioxidant, antihemolytic, antiinflammatory, antidiabetic, and anticancer properties. On top of that, As-ZnO NPs had a high degree of photocatalytic activity against methylene blue dye, with a degradation efficiency of 93.37% within 150 min exposure to sunlight.